Evaluasi Terhadap Pelaksanaan E-Warong Di Kecamatan Padangsidimpuan Tenggara - Rahayu, Rahayu; Zein, Aliman Syahuri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
One of the problems often experienced by developing countries is the problem of poverty, including Indonesia. As an effort to accelerate poverty reduction, since 2007 the Government of Indonesia has implemented the PKH (Family of Hope Program), in which there is a design for the E-Warong (Joint Business Group) KUBE PKH program as a means of accelerating poverty alleviation. This study aims to evaluate the implementation of E-Warong KUBE PKH. This research is a qualitative research, the data sources are primary data and secondary data. The results of this study indicate that the evaluation of the implementation of E-Warong KUBE PKH in Southeast Padangsidimpuan District has not been maximally carried out in accordance with the instructions for implementing E-Warong KUBE PKH, there are several factors that cause the implementation of E-Warong KUBE has not been maximally implemented including, lack of awareness of PKH members towards the responsibility of E-Warong KUBE which causes E-Warong KUBE cannot be said to be successful in increasing the common economy and the lack of understanding of PKH members in using technology, especially in the use of friction machines. As for the contribution in this research, it is hoped that the E-Warong KUBE PKH will be able to evaluate the program so that it runs well and to improve the performance of each PKH member in the future. Key words: Evaluation, Implementation, E-Warong KUBE PKH